A novel diG motif in ORF3a protein of SARS-Cov-2 for intracellular transport - Cruz-Cosme, Ruth; Zhang, Jiantao; Liu, Dongxiao; Mahase, Vidhyanand; Sallapalli, Bhargava Teja; Chang, Peixi; Zhang, Yanjin; Teng, Shaolei; Zhao, Richard Y.; Tang, Qiyi (Frontiers in Cell and Developmental Biology, 2022)
The ongoing SARS-CoV-2/COVID-19 pandemic caused a global public health crisis. Yet, everyone’s response to SARS-CoV-2 infection varies, and different viral variants confer diverse pathogenicity. Thus, it is imperative to understand how viral determinants contribute to COVID-19. Viral ORF3a protein is one of those viral determinants, as its functions are linked to induction of cell and tissues damages, disease severity and cytokine storm that is a major cause of COVID-19-related death. ORF3a is a membrane-associated protein. Upon synthesis, it is transported from ER, Golgi apparatus to plasma membrane and subcellular endomembranes including endosomes and lysosomes. However, how ORF3a is transported intracellularly remains elusive. The goal of this study was to carry out a systematic mutagenesis study to determine the structural relationship of ORF3a protein with its subcellular locations. Single amino acid (aa) and deletion mutations were generated in the putative function-relevant motifs and other regions of interest. Immunofluorescence and ImageJ analyses were used to determine and quantitate subcellular locations of ORF3a mutants in comparison with wildtype ORF3a. The wildtype ORF3a localizes predominantly (Pearson’s coefficients about 0.8) on the membranes of endosomes and lysosomes. Consistent with earlier findings, deletion of the YXXΦ motif, which is required for protein export, retained ORF3a in the Golgi apparatus. Interestingly, mutations in a double glycine (diG) region (aa 187-188) displayed a similar phenotype to the YXXΦ deletion, implicating a similar role of the diG motif in intracellular transport. Indeed, interrupting any one of the two glycine residues such as deletion of a single (dG188), both (dG187/dG188) or substitution (G188Y) of these residues led to ORF3a retention in the Golgi apparatus (Pearson’s coefficients ≥ 0.8). Structural analyses further suggest that the diG motif supports a type-II β-turn between the anti-parallel β4 and β5 sheets and connects to the YXXΦ motif via hydrogen bonds between two monomers. The diG- YXXΦ interaction forms a hand-in-hand configuration that could facilitate dimerization. Together, these observations suggest a functional role of the diG motif in intracellular transport of ORF3a.